Publishing Trends and Libraries - Abbott, John Parsons (DESIDOC Journal of Library & Information Technology, 2004)
Just a few years ago, the death of books and their replacement by e-books was predicted. It didn’t come to pass. Likewise, there are some who are nowpredicting the death of the libraries. The chances are, despite rapid technological changes, libraries will survive into the foreseeable future. http://dx.doi.org/10.14429/dbit.23.1.8014